High Co-infection Status of Novel Porcine Parvovirus 7 With Porcine Circovirus 3 in Sows That Experienced Reproductive Failure - Mai, Jinhui; Wang, Dongliang; Zou, Yawen; Zhang, Sujiao; Meng, Chenguang; Wang, Aibing; Wang, Naidong (Frontiers in Veterinary Science, 2021)
Porcine parvoviruses (PPVs) and porcine circoviruses (PCVs) infect pigs worldwide, with PPV1–7 and PCV2 infections common in pigs. Although PPV7 was only identified in 2016, co-infection of PPV7 and PCV2 is already common, and PPV7 may stimulate PCV2 replication. PCV3, a novel type of circovirus, is prevalent in pig populations worldwide and considered to cause reproductive disorders and dermatitis nephrotic syndrome. In recent studies, pigs were commonly infected with both PCV3 and PPV7. Our objective was to investigate the co-infections between PPV7 and PCV3 in samples from swine on farms in Hunan, China, and assess the potential impacts of PPV7 on PCV3 viremia. A total of 209 samples, known to be positive (105) or negative (104) for PCV3, were randomly selected from serum samples that were collected from commercial swine herds in seven regions from 2016 to 2018 in our previous studies; these samples were subjected to real-time PCR to detect PPV7. Of these samples, 23% (48/209) were positive for PPV7. Furthermore, the PPV7 positive rate was significantly higher in PCV3 positive serum (31.4%, 33/105) than in PCV3 negative serum (14.4%, 15/104). Another 62 PCV3 positive sow serum samples and 20 PCV3 positive aborted fetuses were selected from 2015 to 2016 in our other previous study. These samples were designated as being from farms with or without long-standing histories of reproductive failure (RF or non-RF), respectively, and they were also subjected to real-time PCR to detect PPV7 and to determine whether PPV7 affected PCV3 viremia. Among the 62 serum samples (39 PCV3 positive RF-serum and 23 PCV3 positive non-RF-serum), 45.1% (28/62) were positive for PPV7 and PCV3, and the PPV7 positive rate was significantly higher in PCV3 positive RF-serum (51.2%, 20/39) than in PCV3 positive non-RF-serum (34.8%, 8/23). In addition, there was a higher positive rate of PPV7 (55%, 11/20) in PCV3 positive aborted fetus samples. In addition, the copy number of PCV3 in PPV7 positive samples was significantly higher than that in PPV7 negative serum samples. Based on these findings, we concluded that PPV7 may stimulate PCV3 replication.